Cellular therapies in liver and pancreatic diseases. Issue 5 (May 2023) - Giuli, Lucia; Santopaolo, Francesco; Pallozzi, Maria; Pellegrino, Antonio; Coppola, Gaetano; Gasbarrini, Antonio; Ponziani, Francesca Romana
Abstract: Over the past two decades, developments in regenerative medicine in gastroenterology have been greatly enhanced by the application of stem cells, which can self-replicate and differentiate into any somatic cell. The discovery of induced pluripotent stem cells has opened remarkable perspectives on tissue regeneration, including their use as a bridge to transplantation or as supportive therapy in patients with organ failure. The improvements in DNA manipulation and gene editing strategies have also allowed to clarify the physiopathology and to correct the phenotype of several monogenic diseases, both in vivo and in vitro. Further progress has been made with the development of three-dimensional cultures, known as organoids, which have demonstrated morphological and functional complexity comparable to that of a miniature organ. Hence, owing to its protean applications and potential benefits, cell and organoid transplantation has become a hot topic for the management of gastrointestinal diseases. In this review, we describe current knowledge on cell therapies in hepatology and pancreatology, providing insight into their future applications in regenerative medicine.